1994
DOI: 10.1093/infdis/170.2.377
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa Outbreak in a Burn Unit: Role of Antimicrobials in the Emergence of Multiply Resistant Strains

Abstract: An environmental survey and a cohort study were done to analyze an outbreak of infections in a burn unit caused by a serotype O:11 and a multidrug-resistant serotype O:12 Pseudomonas aeruginosa. The P. aeruginosa O:11 outbreak was controlled by eradicating an environmental source, contaminated hydrotherapy equipment. To assess risk factors for infections caused by P. aeruginosa O:12, 15 infected burn patients were compared with 32 noninfected burn patients hospitalized during the outbreak. Patients had similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
92
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(97 citation statements)
references
References 21 publications
3
92
0
1
Order By: Relevance
“…The MDR AFLP35 strain belonged to serogroup O12. Epidemic strains are frequently of serotypes O11 and O12 (13,14,15,19,43,47,55). Detection of the simultaneous presence of three distinct P. aeruginosa O12 strains, one of which was an environmental strain from the BWC, by AFLP analysis illustrates the advantage of genotyping over serotyping.…”
Section: Downloaded Frommentioning
confidence: 99%
“…The MDR AFLP35 strain belonged to serogroup O12. Epidemic strains are frequently of serotypes O11 and O12 (13,14,15,19,43,47,55). Detection of the simultaneous presence of three distinct P. aeruginosa O12 strains, one of which was an environmental strain from the BWC, by AFLP analysis illustrates the advantage of genotyping over serotyping.…”
Section: Downloaded Frommentioning
confidence: 99%
“…Using several classes of antibiotics to treat infections caused by this bacterium can lead to the emergence of new mutant strains, which have a high level of resistance to many antibiotics [6]. Multidrug-resistant (MDR) Pseudomonas aeruginosa has been described mainly in patients who are immunocompromised, or patients with cystic fibrosis or neoplastic diseases, or patients in Intensive Care Units [7][8][9].…”
Section: Pseudomonas Aeruginosa: Microbiological Clinical and Epidemmentioning
confidence: 99%
“…D espite recent advances in patient care, bacterial infections remain a leading cause of death in severely burned patients (1)(2)(3). In our previous study (4,5) we demonstrated that burn injury suppresses the production of IFN-␥ after Escherichia coli challenge in a mouse model whereas IL-18 treatment restores the IFN-␥ production, thereby improving the survival of burn-injured mice after infection.…”
mentioning
confidence: 93%
“…In our previous study (4,5) we demonstrated that burn injury suppresses the production of IFN-␥ after Escherichia coli challenge in a mouse model whereas IL-18 treatment restores the IFN-␥ production, thereby improving the survival of burn-injured mice after infection. However, many clinical studies have described Pseudomonas aeruginosa and methicillinresistant Staphylococcus aureus, but not E. coli, as the most common agents of postburn infections (1)(2)(3). P. aeruginosa infection especially has a high mortality rate and remains a major cause of death in burned patients (1,2).…”
mentioning
confidence: 99%
See 1 more Smart Citation